طرائق جديدة في عمل أنظمة التبريد والتدفئة باستخدام أنابيب بلاستيكية شعرية - محمود, سمر (Latakia University Journal -Engineering Sciences Series, 2019)
إن التقنيات المطبقة في العمل مستقبلا سيكون لها دور هام في تأمين حماية بيئية كافية و طويلة الأمد عن طريق ترشيد استهلاك الطاقة و الاتجاه إلى استخدام الطاقة البيئية الطبيعية على نطاق أوسع. فالطاقة البديلة يجب أن تكون رخيصة فيما يتعلق بالتكاليف و يجب ألا تسبب أي تلوث إضافي للبيئة في أثناء التصنيع و التشغيل والتخلص من الفضلات. وقد تم تطوير تكنولوجيا الأنابيب الشعرية باستخدام مادة البولي بروبيلين [1]، و هي مادة بلاستيكية يمكن استخدامها في عمليات التدفئة بالماء الساخن (من الطاقة الشمسية أو من المراجل ) و التبريد بالماء البارد (من مياه الآبار أو البحار أو من مبردات الماء) الذي يمرر عبر شبكة من الأنابيب الشعرية المصنوعة من مادة البولي بروبيلين المرن و التي يتم تركيبها ضمن سقف الغرفة و تحت البلاط أو على الجدران إذ تغطي الأسطح بالكامل. وهذا يلطف حرارة السقف و الأرضية و الجدران. بسبب مساحة سطح الأنابيب الشعرية الكبير فإنها تكون أكثر فعالية للتوزيع الحراري المتجانس . ونتيجة لتطبيق الدراسة وأختبار النظام الجديد في التدفئة و التبريد تم الحصول على نتائج جيدة و فوائد كثيرة من حيث التشغيل و الامان و الكلفة : تشغيل أفضل _ تجميع أسهل _ سلامة تشغيلية أعلى _ تكلفة أقل _مستويات تلوث أقل . The applied techniques of future work will have an important role in ensuring adequate, long-term environmental protection through energy efficiency and the tendency for a wider use of natural environment. Energy is the alternative and must be cheap with respect to costs and should not cause any additional pollution of the environment during manufacturing, operation, and disposal of waste. The technology of capillary tube has been developed using a polypropylene[1], which is a plastic material that can be used in heating with hot water (solar or boiler) and cooling with cold water (water obtained from wells, the sea, or water coolers) which passes through the network of the capillary tube made of flexible polypropylene, installed within the ceiling of the room and under the tiles or on the walls to cover the surfaces completely. This cools the temperature of the ceiling, the floor, and walls. Because the surface area of capillary tube is big, there is a more effective distribution of homogenized heat. As a result of the application of the study and test, the new system for heating and cooling is to get good results and many benefits in terms of operation, safety and cost: easier compilation, easier running, higher operational safety, lower cost, lower pollution levels.